PROSPEK WISATA HALAL DI KOTA MALANG: SEBUAH TINJAUAN ATAS PELUANG DAN TANTANGAN - Aprillia Rahmadian; Mochammad Musafa'ul Anam (Jurnal Pariwisata Pesona, 2021)
Malang City was chosen as the leading destination for national halal tourism because the concept of halal tourism that has been owned by Malang city since 2018 has matured. Apart from that, the large number of both foreign and domestic tourists is also a determining factor. The purpose of this study is  to find out the opportunities and challenges of halal tourism in Malang. There are so many opportunities and potentials in developing halal tourism programs, as well as the challenges faced by tourism stakeholders are getting bigger. This is what underlies this research,  to find out opportunities and challenges in the development of halal tourism in the Malang city. The type of research design is exploratory and qualitative research. Exploratory research is a research design that explores situations or situations to gain insight and understanding. The results of this study are several points of opportunity from halal tourism: 1) Halal tourism is already popular in foreign markets. (Malaysia, Singapore, Middle East), 2) increasing public awareness in adopting a halal lifestyle, 3) the variety and number of tourist attractions (halal) which are popular with foreign tourists, 4) the potential for adequate infrastructure and accommodation in Malang city. Meanwhile, some challenges in halal tourism include; 1) the quality of halal tourism infrastructure in competing countries is relatively better, 2) halal tourism has been affected by the Covid-19 pandemic.